A microRNA-related single nucleotide polymorphism of the Dicer gene is associated with risk of dermatomyositis - Peng, Chenxing; Zhang, Jingjing; Zhang, Shasha; Zhang, Xiaoyun; Zhao, Yufei (European journal of inflammation, 2023)
Objectives: To evaluate the correlation of miRNA-related single nucleotide polymorphisms (miR-SNPs) with the risk of dermatomyositis (DM) development. Introduction: MicroRNAs (MiRNAs) are involved in a variety of activities such as cell differentiation, proliferation, apoptosis, tumorigenesis, and immunological response. MiR-SNPs alter the expression levels of miRNAs, leading to increased susceptibility to DM. Methods: We genotyped six miR-SNPs for miRNA processing machinery genes, including XPO5 (rs11077), RAN (rs14035), Dicer (rs3742330), TNRC6B (rs9623117), GEMIN3 (rs197412), and GEMIN4 (rs2740348), and two miR-SNPs for microRNA binding site, including SET8 (rs16917496), and KRT81 (rs3660), in a case-control study to assess the impact of these miR-SNPs on DM risk. Then we assessed cytokine expression and ROS levels in DM to determine the relationship between risk-related miR-SNPs and cytokines. Results: We discovered that Dicer’s (rs3742330) AA genotype had a decreased chance of developing DM than the AG + GG type (odds ratio, 0.527; 95% confidence interval: 0.281–0.987; p = 0.045). The subsequent analysis showed that the AA genotype carrier had greater levels of IL-4 (p = 0.034). Conclusion: The SNP of Dicer (rs3742330) maybe an attractive predictor of DM, moreover the cytokine of IL-4 may act as the factor that distinguishes SNP of Dicer (rs3742330) into AA and AG + GG.